KERAGAMAN GASTROPODA YANG MENDAPAT MASUKAN LIMBAH TAHU-TEMPE DI KALI ANCAR - Diniarti, Nanda (Program Studi Biologi FMIPA Universitas Mataram, 2015)
Ancar is one of the streams that cross the city of Mataram. In the downstream, especially when entering into Kekalik Jaya, Ancar river getting input liquid and solid wastes from the tofu and tempeh home industry. The slightest input on water will affect the biota that inhabit in this gastropoda. This study was to determine the types of gastropods that inhabit the waste input. Sampling was conducted in 2006, 2009 and 2011. The observation area of waste originated in Kekalik Swadaya until Kekalik Gerisak. Gastropods were obtained as much as 6 family and Thiaridae a family with the highest density and appearance in each observation station. Family Thiaridae please waters containing high organic matter.Keywords: Density, gastropods, Ancar river, Thiaridae